2022
DOI: 10.1177/03611981221095526
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different Penetration Rates of Shared Autonomous Vehicles on Traffic: Case Study of Budapest

Abstract: The accelerating emergence of vehicle automation and the anticipation of the advent of shared mobility through fully autonomous vehicles indicate the beginning of a new era of mobility which has the potential to reshape the future of transport in urban areas. In light of such developments, it is important that communities prepare to adapt to the changes they might entail. Therefore, in this paper, traffic flow theory, simulation-based dynamic traffic assignment, and a computer experiment using PTV Visum softwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…where O n is the number of commuters passing daily through the network segment n ∈ N, P is the population in the town or adjacent territories from where the workers will arrive, E is the employment-to-population ratio, P a is the number of people who can access the job places at a fixed distance calculated by Equation (20), k c is the travel mode coefficient for the cycling travel mode (desired or measured), D is the total number of jobs in the destination area.…”
Section: The Micro-scale Origin-destination Methods For Forecasting B...mentioning
confidence: 99%
See 1 more Smart Citation
“…where O n is the number of commuters passing daily through the network segment n ∈ N, P is the population in the town or adjacent territories from where the workers will arrive, E is the employment-to-population ratio, P a is the number of people who can access the job places at a fixed distance calculated by Equation (20), k c is the travel mode coefficient for the cycling travel mode (desired or measured), D is the total number of jobs in the destination area.…”
Section: The Micro-scale Origin-destination Methods For Forecasting B...mentioning
confidence: 99%
“…This situation can be attributed to traditional transport planning methods that calculate traffic flows between transportation districts without considering local street segment-level changes, but traditional methods are not sensible to micro-level or pathway segment-level changes. The present generation of traffic planners often relies on macro-level data, despite advancements in processing speed and data capacity [19][20][21][22]. Micro-simulation, typically performed with software such as PTV VISIM, analyses changes in existing traffic flows, link delays, volumes, and traffic light phases [23,24], but often fails to provide detailed predictions at the neighborhood level.…”
Section: Introductionmentioning
confidence: 99%
“…A study that accommodated ride-sharing options for a fully electric SAV fleet, as the adoption of electric vehicles is growing worldwide [84], investigated the implications of SAVs on the performance of the Budapest road network using simulation-based dynamic traffic assignment. The results showed that increasing the SAVs share would improve the overall network performance [85]. An analysis of the potential benefits of dynamic ride sharing using SAVs over traditional taxis in New York City demonstrated that the fleet size could be reduced by 59% without increasing the waiting time.…”
Section: Adoption Of Savsmentioning
confidence: 99%
“…Some researchers tend to create several scenarios to cover the possible cases of integrating AVs into road networks as this new technology is not yet entirely developed (see e.g. [10][11][12][13]), which consumes time and effort.…”
Section: Introductionmentioning
confidence: 99%